Personality Traits, Burnout, Workplace Bullying and Sleep Quality Among Midwives: A Pilot Study - Simona Dobešová Cakirpaloglu; Jiří Vévoda; Panajotis Cakirpaloglu; Šárka Vévodová; Peta Jane Greaves; Dorota Folwarczná (Nursing Open)
ABSTRACT Aim The work of midwives is often mentally and physically exhausting. We sought to determine whether an association exists between personality traits, burnout syndrome, bullying in the workplace, and sleep quality. Additionally, we aimed to assess whether personality traits, dimensions of burnout, and sleep quality differ between a group of bullied and non‐bullied midwives. Design A cross‐sectional, correlation study was conducted. Methods The research sample consisted of 71 midwives, average age 36 years, average length of practice 14.23 years. Data were collected using a demographic questionnaire, Maslach Burnout Inventory (MBI), Negative Acts Questionnaire—revised (NAQ‐R), International Personality Item Pool: Big Five Markers—50 (IPIP‐BFM‐50) and Pittsburgh Sleep Quality Index (PSQI). Results There was a significant relationship between personality traits, workplace bullying, the dimensions of burnout, and poor sleep quality. There were significant differences in extroversion, emotional stability, emotional exhaustion, and sleep quality between those midwives that experienced workplace bullying and those that did not. Victims of workplace bullying tended to be more neurotic and less extroverted than non‐victims. Conclusion The study findings indicate that personality traits may function as both predictors and outcomes of workplace bullying. There was no patient or public contribution.